IMPACT OF FOLIAR-APPLIED DORMANCY-BREAKING AGENTS ON FLOWERING BEHAVIOR, YIELD, FRUIT QUALITY, AND SOME CHEMICAL CONSTITUENTS OF “EIN SHAMER” APPLE TREES - EL-YAZAL, MOHAMED A SEIF; EL-YAZAL, SAMIR A SEIF (Innovare Journal of Agricultural Sciences, 2021)
Objective: This investigation was carried out during the two successive seasons of 2016 and 2017 to investigate the effect of Dormex, mineral oil, potassium nitrate, calcium nitrate, and thiourea on bud break, growth, yield, and some chemical constituents of “Ein Shamer” apple (Malus sylvestris, Mill) variety. Methods: The trees were grown in loamy sand soil, and sprayed with six treatments (Dormex (4%), mineral oil (5%), potassium nitrate (8%), calcium nitrate (8%), and thiourea (2%) and control. Results: In general, it was found that all studied growth parameters, date of flower bud break, percentage of bud break, fruit-setting, fruit weight, fruit size, fruit number/tree, yield/tree (kg), and some chemical constituents of leaves (total chlorophyll, total carbohydrates, total protein, nitrogen, phosphorous, and potassium contents) and some chemical constituents of fruits total soluble solids (T.S.S.), T.S.S./acid ratio, Vitamin C, water content %, total free amino acids, total carbohydrates, total sugars, and reducing sugars) were increased with the application of the different treatments. Conclusion: The best results were obtained from the treatment of Dormex at 4% and mineral oil (5%). On the contrary, the same treatment decreased total acidity and total phenols in fruits as compared to the control. It could be recommended to use Dormex at 4% and mineral oil (5%) for improving bud break, growth, yield, and chemical constituents of apple trees or fruits.